An integrated UMAS for POME treatment - N. H., Abdurahman; Azhari, H. Nour (IWA Publishing, 2018)
The direct discharge of palm oil mill effluent (POME) wastewater causes serious environmental hazards due to its high chemical oxygen demand (COD) and biochemical oxygen demand. This paper proposes a new approach for integrated technology of ultrasonic-membrane for a POME treatment. The paper evaluated the economic viability based on the changes of the new design of ultrasonic-membrane anaerobic system when a POME introduces this approach. Six steady states were attained as a part of a kinetic study that considered concentration ranges of 13,800–22,600 mg/L for mixed liquor suspended solids and 10,400–17,350 mg/L for mixed liquor volatile suspended solids. Kinetic equations from Monod, Contois and Chen and Hashimoto were employed to describe the kinetics of POME treatment at organic loading rates ranging from 1 to 15 kg COD/m3/d. throughout the experiment, the removal efficiency of COD was from 92.8 to 98.3% with hydraulic retention time from 500.8 to 8.6 days. The growth yield coefficient, Y, was found to be 0.73 gVSS/g COD the specific microorganism decay rate was 0.28 day–1 and the methane gas yield production rate was between 0.27 and 0.62 L/g COD/d.